Fa’aliyatu Istikhdam Washilah Ash-Shuwar li Tarqiati Kafaati Ath-Thullab ‘ala Al-Mufradat - syukri, Ahmad Syukriansyah; Marsiah; Aulia Mustika Ilmiani (Program Studi Pendidikan bahasa Arab IAIN Langsa, 2025)
This research stems from the importance of mufrodat mastery in children's language development, especially for children aged 8-12 years. One method that can be used to improve the mastery of mufrodat is the use of picture media, which can stimulate thinking and facilitate the understanding of language concepts. This study aims to determine the effectiveness of using picture media in improving the mastery of mufrodat for children aged 8-12 years. This research used descriptive quantitative method of experimental type with Pre-Experimental Design approach with One-Group Pretest-Posttest. Data were collected through mufrodat mastery tests before and after treatment and observation during the learning process. Data analysis used descriptive statistical data analysis and used the N-Gain Score value and strengthened with the Paired Sample Test Parametric test to find the effectiveness of increasing mastery of mufrodat before and after being given image media. The results showed that the average score of 18 participants on the pretest was 42 while the average on the posttest was 73, and the N-Gain Score value showed an average result of 0.5659 which means that the acquisition of the N-Gain Score value entered the medium category and a percentage of 57% with a fairly effective interpretation. And the results of the Paired Sample t-Test hypothesis test show the results of Asymmp. Sig. (2-tailed) is 0.000. Because the value of 0.000 is smaller than <0.05, it can be concluded that â€œHa is acceptedâ€. This means that there are results of increasing mastery of mufordat for pretest and posttest, so it can be concluded that â€œthere is an increase in children's mastery of mufrodat in learning Arabic by using picture media in the Thematic KKN program in Sukamulya Complex Kel. Tangkiling Kec. Bukit Batu Kota Palangka Raya.